Standards And Norms Of Human Rights-Based Land Administration Services - Pasamai, Syamsuddin (Al-Makki Publisher, 2025)
This study discusses the importance of standards and norms of human rights-based land administration services within the framework of the Indonesian state of law. Land administration services as part of public services must meet the principles of legal certainty, justice, and non-discrimination as mandated by Law Number 25 of 2009 concerning Public Services and Law Number 39 of 1999 concerning Human Rights. This research highlights the challenges of implementing land administration services that have not been fully handed over to local governments, thus causing a gap between regulations and practices in the field. It was also emphasized the need to implement Minimum Service Standards (SPM) that ensure access and quality of services to the community, especially in ensuring legal protection of land owned or controlled by citizens.